ANALISIS PERBEDAAN GAYA BELAJAR WARGA BELAJAR PENDIDIKAN KESETARAAN WILAYAH PEDESAAN DAN PERKOTAAN DI PKBM AL-IKHRAM - Ibnu Hajar; Sardi Pranata; Anifah; Ayu Wulandari Siregar; Tri Oktavia Siregar; Agnes Ginting; Vena Febiola Risdianto; Miranda Afriza; Dhea Putri Cindriani Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the differences in learning styles among equivalency education learners (Warga Belajar) residing in urban and rural areas at PKBM Al-Ikhram. The background of this study is rooted in the importance of understanding learning styles as a contextual factor that influences learning effectiveness, particularly in equivalency education where participants have highly diverse social backgrounds, ages, motivations, and learning experiences. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The findings indicate that learners in urban areas tend to have visual and reading-writing learning styles, which is influenced by better access to technology and learning media. Conversely, learners in rural areas predominantly use kinesthetic and auditory learning styles, which are closely related to direct experience and verbal social interaction. These differences are also influenced by environmental factors, age, motivation, and the availability of learning facilities. This finding emphasizes the importance for the mentors or tutors in equivalency education to understand and adjust their teaching methods to the learners' styles to ensure the learning process is more effective and meaningful.